Impact of the transportation infrastructure on the competitiveness level of Ecuadorian companies in the global market - Caldatto, Mateo Jose Jaramillo (2019)
Competitiveness is one of the most important advantage when a country wants to persevere in the global economy. Latin-America has been relegated from the economic growth in the last decades. There are several reasons why the region has not been able to catch up with the rest. As a matter of fact, logistics costs for the region has been rising. As a result, companies and countries have lost competitiveness against other countries where the development of transportation infrastructure has decreased logistics costs. The world economic forum developed a study where it compares competitiveness between countries. It contains 12 pillars that influence the final outcome. In fact, one the main pillars is transportation infrastructure. The study objective was to determine the impact of the development of transport infrastructure in Ecuadorian companies. The methodology used was through interviews to important key business and academic people with knowledge and experience in the field. The study was able to determine that lack of innovation, corruption, and the dependence of the exploitation of natural resources has affected the development of transport infrastructure in Ecuador. As a result, Ecuadorian companies competing in the global market can encounter strong competition.